The Gentle Prodigal - Kpolugbo,Stella N (Spectrum Books Ltd, 2003)
This story revolves around a boy, Martin who was sent to school but misplaced his priority. Instead of facing his studies squarely, he was always in the company of bad students.
Keywords: Juvenile Fiction; Life Experiences; Realistic